Janus kinase inhibitors for alopecia areata: a review of clinical data - Sun, Yutong; Li, Qian; Zhang, Yanli; Liu, Yaling (Frontiers in Immunology, 2025)
Alopecia areata (AA) is an autoimmune disease characterized by inflammatory and non-scarring hair loss, mediated by CD8+ T cells and primarily affecting hair follicles. Janus kinase (JAK) inhibitors selectively inhibit JAK, block the signal transducer and activator of transcription pathway, and often interfere with T-cell-mediated inflammatory cytokine pathways. They are a class of targeted anti-inflammatory drugs that can promote the activation of hair follicle stem cells. Studies have shown that JAK inhibitors exhibited good efficacy and safety in the treatment of AA, with fewer serious side effects. This article reviews the mechanism of action of JAK inhibitors in the treatment of AA and the effects and side effects of representative drugs.